Nearby M subdwarfs from LAMOST data release 2. (July 2016) - Bai, Yu; Luo, A-Li; Comte, Georges; Zhao, Jing-Kun; Yang, Hai-Feng; Guo, Yan-Xin; Wang, You-Fen; Li, Yin-Bi; Du, Bing; Hou, Wen; Kong, Xiao; Yi, Zhen-Ping; et al.
Abstract: We identify 108 M subdwarfs (sdMs) out of more than two hundred thousand M type spectra from the second data release (DR2) of the LAMOST regular survey. This sample, among which 58 members are identified for the first time, includes 33 extreme subdwarfs (esdMs) and 11 ultra subdwarfs (usdMs). The selection is based on the usual ratio of absorption depth of CaH2, CaH3 and TiO5 band systems. We also emphasize the use of the CaH1 band. We provide estimates of spectral subtype (SPT), Lépine metallicity index ζ, effective temperature and [Fe/H]. Both ζ—[Fe/H] and SPT— T eff figures show reasonable consistency; compared to PHOENIX model spectra, average rounded values of [Fe/H] for sdMs, esdMs and usdMs are respectively −0.5, −1 and −1.5. The photometric distances are estimated, indicating that most sources are located within 500 pc of the Sun and 350 pc of the Galactic disk. Velocities and 3D Galactic motions are also briefly discussed. Among the 108 subdwarfs, seven stars appear to be active with a significant Hα emission line. The source LAMOST J104521.52+482823.3 is a white dwarf - M subdwarf binary, while LAMOST J123045.52+410943.8, also active, exhibits carbon features in red.